Improving the Learning Outcomes of History of Pre-Literacy Life Materials in Indonesia Through the "Grace Door" Quiz for Students of Class X IPS 1 SMA N 1 Banjarnegara - Utari, Sri (Indonesian Journal of History Education, 2021)
The Target of this research is to know how to apply the Quiz " Pintu Rahmat" by a class student of X Social Sciences 1 SMA Country 1 Banjarnegara school year 2014 / 2015. This research type is Research of Action Class, which has activity steps consisting of two cycles. Research data was obtained using etiquette and perception with a perception sheet and [pass/through] evaluation tests. The technique used to analyze data is to use descriptive statistical analysis modestly by using mean [count/calculate]). Results of the research show to [pass/through] Quiz " Pintu Rahmat," obtained by the fact the result of learning history mount. The class average value before the research was 76,92, and the total learned value was only 59%. After conducting action in cycle I, the class average value goes up to 80,77, thoroughly learned to reach 67%. In contrast, in cycle II, the natural class average value [is] equal to 81,66, thoroughly learned to reach 78%. This research suggests that Kuis "Pintu Rahmat" must be executed in class because the study model can improve the understanding of the student's results and the live lines of student mount.